Interaction in the Tradition of Tolak Balak by Juru Ladi at a Javanese Traditional Wedding: An Ethnolinguistic Study - Dela Adeliya; Nur Fateah (Yayasan Keluarga Guru Mandiri, 2024)
This study explores the tradition of “tolak balak” (warding off bad luck) by “juru ladi” (female traditional leaders) in Javanese traditional wedding ceremonies in one village in Central Java, Indonesia, through an ethnolinguistic approach. Using a qualitative descriptive method, data were collected through observation and interviews. Data analysis was conducted to identify the form and meaning of linguistic units and local wisdom. This research aims to provide a deeper understanding of the richness of local culture and give new insights into ethnolinguistics. The study findings reveal various forms and meanings of linguistic units that illustrate the community's cultural wealth and local wisdom, such as words, phrases, and discourse. Words include multiple terms and objects used in ceremonies, such as offerings, traditional tools, ritual feasts, and food. In addition, phrases are used in the